Enhanced production of l-fuculose by Escherichia coli engineered via genome-scale metabolic modeling - Gun-Hwi Yeon; Du-Kyeong Kang; Hyun-Jin Koo; Daewon Go; Jungyeon Kim; Bong Hyun Sung (PLoS ONE, 2026)
l -Fuculose is a rare deoxyketohexose sugar and is a structural isomer of l -fucose, which exhibits skin-lightening, moisturizing, and anti-aging effects. Due to their structural similarity, l -fuculose is also expected to provide potential health benefits. However, l -fuculose exists only in trace amounts in nature, making extraction from natural sources virtually impossible; to date, it has been synthesized mainly by enzymatic conversion. This approach, however, suffers from major limitations: both the substrate ( l -fucose) and the enzyme involved ( l -fucose isomerase) are costly; the enzymatic reaction cannot achieve complete conversion due to the chemical equilibrium; and the methods for purification of l -fuculose from the reaction mixture containing both l -fucose and l -fuculose are inefficient and uneconomical. Microbial cell factories have been explored as an alternative route for l -fuculose biosynthesis, but their production titers remain extremely low, limiting their industrial applicability. In this study, a microbial cell factory was engineered in Escherichia coli by redirecting the pathway of l -fucose metabolism toward l -fuculose production. Overexpression of fucA enabled the aldol condensation of lactaldehyde and dihydroxyacetone phosphate to produce l -fuculose-1-phosphate, which was subsequently dephosphorylated to l -fuculose by a sugar phosphatase. To prevent diversion of substrates and products into competing pathways, the fucI , fucK , tpiA , fucO , and aldA genes were deleted. The final engineered strain produced 50.25 ± 4.30 mg/L of l -fuculose, a 32.4-fold increase compared to that achieved previously by microbial biosynthesis. This study establishes a foundation for the industrial production of l -fuculose, which has potential application as a valuable ingredient in cosmetics, functional foods, and pharmaceuticals.